(untitled) (Research, Society and Development, 2020)
The aim of the present study was to evaluate the physical-chemical profile of raw sheep milk and the influence of storage temperature on the population of microorganisms. Sheep milk samples were collected from the milk cans (500 mL/sample) and were evaluated the physical-chemical composition: fat, protein, lactose, ash content, total dry matter (TDM), cryoscopy index (°H), titratable acidity, and somatic cell count (SCC). After the samples were stored at 4°C and 9°C (72 h) and the titratable acidity, the population of the deteriorating microorganisms and quality indicators were determined. PetrifilmTM (3M do Brasil Ltda) were used for the mesophilic aerobic count (37°C/48 h), total coliforms (37°C/24 h), Escherichia coli (37°C/48 h), and enterobacteria (37°C/24 h). For psychrotrophic bacteria, was used Plate Count Agar (7ºC/10 days) and for Pseudomonas spp., CFC-supplemented Pseudomonas agar base (25ºC/48 h). Average values for raw milk were 6.28% fat, 83.46% moisture, 16.52% TDM, 0.92% ash, 5.30% protein, 4.43% lactose, a cryoscopy index of -0.575°H, and SCC of 3.38 x 106 cells/mL. Milk acidity values were higher (0.24 g lactic acid/100 ml) with 72 hours of storage. The higher the temperature and/or storage time, the higher the counts of psychrotrophic, Pseudomonas spp., and enterobacteria, for mesophilic aerobic only the storage time. Refrigeration at 4ºC and a reduction of storage time are important to control the microorganism’s population that compromise the quality, shelf life, and food safety of sheep milk and dairy products.